Impact of Foliar Fertilizer Application on Three Genotypes Corn (Zea mays) Nutrient Efficient in Tidal Lands - Andesta; Ida Aryani; Midranisiah; Neni Marlina (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Corn is a strategic food commodity with increasing demand, necessitating enhanced production through optimized fertilization, especially in marginal lands such as tidal areas. This study aims to evaluate the effect of foliar fertilizer application on three corn genotypes and its impact on nitrogen fertilizer use efficiency in tidal lands. A split-plot design with three factors was employed: the first factor was corn genotype; the second factor was urea fertilizer dose (0 kg, 255 kg, and 310 kg per hectare); and the third factor was foliar fertilizer treatment, which included no spraying (control), spraying on the 30th day, the 45th day, both the 30th and 45th days, the 60th day, the 75th day, and both the 60th and 75th days. Each treatment was replicated three times. The results indicated that applying 300 kg of urea fertilizer per hectare, combined with foliar fertilizer, positively influenced the growth of the G3 corn genotype and resulted in a high yield in tidal lands. This treatment produced 7.44 tons of corn per hectare, a significant increase compared to other treatments, making it an efficient strategy for enhancing corn productivity in tidal areas. It is recommended that farmers in tidal regions use a combination of 300 kg urea per hectare and foliar fertilizer applications to optimize corn yields.